Mathematics and literature from zero to three: A tale of storks (Edma 0-6: Educación Matemática en la Infancia, 2021)
From the elements of the surrounding environment both physical and cultural, we can deal with mathematical concepts related to classification and formation of sets. Using as a starting point the reading of “The book of autumn” and “A tale of storks”, we will try to make classifications using as base concept formation. We will make, with children, simple groupings using equivalence relations.
Keywords: Zero to three; Mathematics; Children's literature; Classification; Equivalence relations; Sets